Patient safety and performance of dietician profession in Poland - Marcin Mikos; Aleksandra Izabela Czerw; Grzegorz Juszczyk (Kazimierz Wielki University, 2017)
A dietitian is a qualified health care professional who has extensive knowledge in the nutrition of healthy and ill people. By selecting the right diet, the specialist carries out the prevention of diet-related diseases and is responsible for nutritional treatment in various conditions. Dietitian also disseminates knowledge about proper nutrition [1]. In the context of public health problems such as malnutrition and overweight and obesity, nutritionists play an extremely important role, complementary to the treatment, care and physiotherapy of patients in hospitals. Proper nutrition determines the whole process of providing health services; Its effectiveness, quality and patient safety. Despite the great role and responsibility of dieters, this profession remains practically outside of the legal field in Poland. At present, regulated next to the doctor, nurse, pharmacist and laboratory diagnostician, also a physiotherapist and a medical rescuer. Due to the patient's safety, the lack of uniform standards of education for the dietician, which corresponds to precisely defined professional competences, is particularly pertinent to the legal framework obliging a dietitian, like a physiotherapist to exercise his profession properly, in accordance with current medical knowledge, with due diligence and care Patient safety. There are also no provisions obliging dieticians to continue education, professional recertification in the case of breaks in the profession. In the health system there is also no institution responsible for substantive supervision and custody of the proper exercise of this profession. At this time, there may be numerous types of adverse events in the profession of a dietitian in the treatment of a health-care professional. The assessment of the impact of the profession of dietitian on patient safety was based on an analysis of the medical law on the medical profession and on the quality of the treatment process. The work will analyze the occurrence of adverse events in dietetics in the light of the case law of the common courts.